THEORETICAL APPROACH TO THE SCIENTIFIC WORKS ON PUNCTUATION - Halimova Nodirabonu; Samigova Xushnuda (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Punctuation - punctuation marks are of special importance in the formation and improvement of writing culture. Punctuation marks are extremely important in expressing various mental relations, psychological and intonation states that cannot be expressed by other means of writing (letters, numbers, diacritical marks) and language units (words, morphemes).